Risk Attitudes and Migration - Mehtap Akgüc; Xingfei Liu; Massimiliano Tani; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2015)
To contribute to a scarce literature, in particular for developing and emerging economies, we study the nature of measured risk attitudes and their consequences for migration. We also investigate whether substantial changes in the risk environment influences risk tolerance. Using the 2009 RUMiC data for China, we find that rural-urban migrants and their family members are substantially less risk-averse than stayers. We further provide evidence that individual risk attitudes are unaffected by substantial changes in the environment and that risk tolerance is correlated across generations.
Keywords: J61; D81; 330; migration; risk attitudes; risk aversion; China